Influence of trajectories on the joint torques of kinematically redundant manipulators - Khang, Nguyen Van; Tuan, Do Anh; Dien, Nguyen Phong; Nam, Tran Hoang (Vietnam Journal of Mechanics, 2007)
This paper presents an algorithm for solving the inverse dynamics problem of redundant manipulators using MAPLE software. The method has the advantage of generating efficient symbolic solutions which reduces the computational cost. The influence of trajectories on the joint torques of redundant manipulators is considered. The theory is illustrated by the numerical simulation of a redundant four-link planar manipulator.